2019
DOI: 10.1051/0004-6361/201935220
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Lidov-Kozai resonance for an outer test particle due to an eccentric perturber

Abstract: Aims. We analyze the behavior of the argument of pericenter ω 2 of an outer particle in the elliptical restricted three-body problem, focusing on the ω 2 resonance or inverse Lidov-Kozai resonance. Methods. First, we calculate the contribution of the terms of quadrupole, octupole, and hexadecapolar order of the secular approximation of the potential to the outer particle's ω 2 precession rate (dω 2 /dτ). Then, we derive analytical criteria that determine the vanishing of the ω 2 quadrupole precession rate (dω … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The eccentric Lidov-Kozai oscillation in the outer problem is also formulated, and applied to solar system dynamics (e.g. Naoz et al, 2017;Zanardi et al, 2017;Vinson and Chiang, 2018;de Elía et al, 2019). Here again, we insist that this line of orbital phenomenon should be called, consistent with our discussion, the eccentric von Zeipel-Lidov-Kozai oscillation.…”
Section: Von Zeipel-lidov-kozai Oscillationsupporting
confidence: 66%
“…The eccentric Lidov-Kozai oscillation in the outer problem is also formulated, and applied to solar system dynamics (e.g. Naoz et al, 2017;Zanardi et al, 2017;Vinson and Chiang, 2018;de Elía et al, 2019). Here again, we insist that this line of orbital phenomenon should be called, consistent with our discussion, the eccentric von Zeipel-Lidov-Kozai oscillation.…”
Section: Von Zeipel-lidov-kozai Oscillationsupporting
confidence: 66%
“…All planets around eccentric binaries experience inclination oscillations that take place over tens of thousands of years as a result of the asymmetric potential of the binary (Verrier & Evans 2009;Farago & Laskar 2010). Previous test particle studies reveal complex dynamics due to a set of resonances with an interior perturber that induce large oscillations in particle eccentricity and inclination as well as librating orbits (orbits whose argument of periapsis oscillates about a fixed point) and orbit flipping (orbits that flip from prograde to retrograde) of the test particle (Naoz et al 2017;Vinson & Chiang 2018;de Elía et al 2019). Such resonances can lead to the chaotic and unstable evolution of a body and explain the semi-major axis dependence on eccentricity variation we observe in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that the orbit of the outer star is affected by the inverse-KL and other eccentricityinclination resonances(e.g. de Elía et al 2019;Naoz et al 2017Naoz et al , 2020Vinson & Chiang 2018), which may enhance the outer eccentricity effectively, depending on the initial conditions. For example, Vinson & Chiang (2018) showed that the eccentricity of an outer test particle can be enhanced up to ∼ 0.2 and ∼ 0.3 by the inverse KL resonance and octupole resonance on out + in −2Ω out , respectively.…”
Section: Discussionmentioning
confidence: 99%